Pengaruh Motivasi, Lingkungan Kerja, Organizational Citizenship Behaviour terhadap Kepuasan Kerja Karyawan Pt. Pentel Siporio di Makassar - Rahma Muthia; Baso Amang; Junaiddin Zakaria (Journal on Education, 2023)
This study aims to examine empirically the influence of motivation, work environment and organizational citizenship behavior on job satisfaction of PT Pentel Siporio employees in Makassar. The population used is employees of PT. Pentel Siporio in Makassar, who have worked for three consecutive years, namely in 2019, 2020 and 2021. With a total population of 105 people, samples were drawn based on the solving formula, finally 51 people were obtained. employees who were used as respondents. This research is a quantitative and qualitative research using primary data. The hypothesis test used is Multiple Linear Regression Analysis. Data is processed through the Statistical Product and Service Solution (SPSS) Program. The results of this study indicate that Motivation, Work Environment and Organizational Citizenship Behavior are based on the results of a Simultaneous test or testing simultaneously with the three variables Motivation (x1), Work Environment (X2) and Organizational Citizenship Behavior (x3), so the results have a positive and significant effect on job satisfaction Employees of PT. Pentel Siporio in Makassar.